Reliability of Hand-Held Dynamometer in Measuring Gluteal Muscle Rate of Torque Development and Peak Torque: Push and Pull Configurations - Takhyun Yoo; Sungwan Kim; Julie P. Burland; Neal R. Glaviano (International Journal of Sports Physical Therapy)
# Background